IMPACT OF PANAMA SCANDAL ON KARACHI STOCK EXCHANGE: AN EVENT STUDY METHODOLOGY - Dr. Majid Ali, Dr. Muhammad Ramzan, Dr. Muhammad Usman, Nosheen Pervaiz, Faheem Fazal (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The proposed study is an empirical study and comparatively analysis the impact of panama scandal and its decision on Karachi stock exchange (Pakistan Stock Exchange). The main objective of this study is to analysis the impact of an event on the stock of the market. To achieve this objective, data have been taken from [1]Yahoo. Finance Website for the period of 3 years, ranging from 2015-2017. Event study methodology is used for this analysis. For calculating AR, AAR, and CAAR, different descriptive techniques of Microsoft Excel is used. A window of 11 days (5 days before and 5 days after the announcement and the date of the announcement of the decision) is taken to examine the joint reaction to the Panama decision. The results show that there has been an increase in the share price and has resulted in a positive average abnormal return, especially after the declaration of the decision in the Pakistan period.